COMPARING THE PHRASEOLOGICAL UNITS DEFINING HUMANITY IN ENGLISH AND UZBEK LANGUAGES - Khudayberdieva, Zarrinanobu (INTERNATIONAL CONFERENCES, 2023)
Phraseologism - stable in composition and structure, lexically indivisible and integral in meaning, a phrase or sentence that performs the function of a separate lexeme (vocabulary unit). Phraseology and phraseological units are characteristic of all languages of the world. This is a huge layer of both English and Uzbek languages.